alguém pelo amor de Deus me ajuda????
Anexos:
Soluções para a tarefa
Respondido por
1
(a + b)^2 é o mesmo que (a + b) . (a + b)
E também (a + b)^2 = a^2 + 2ab + b^2
Letra a)
(9h^3 + 5t^4) = (9h^3)^2 + 2(9h^3*5t^4) + (5t^4)^2 = 81h^6 + 90h^3*t^4 + 25t^8
Letra b)
(2/7x^5 + 4/3y^9)^2 = (2/7x^5)^2 + 2( 2/7x^5*4/3y^9) + (4/3y^9)^2 = 4/49x^10 + 16/42x^5*y^9 + 16/9y^18
( notação: ^ (elevado) ; / (divisão, fração) )
E também (a + b)^2 = a^2 + 2ab + b^2
Letra a)
(9h^3 + 5t^4) = (9h^3)^2 + 2(9h^3*5t^4) + (5t^4)^2 = 81h^6 + 90h^3*t^4 + 25t^8
Letra b)
(2/7x^5 + 4/3y^9)^2 = (2/7x^5)^2 + 2( 2/7x^5*4/3y^9) + (4/3y^9)^2 = 4/49x^10 + 16/42x^5*y^9 + 16/9y^18
( notação: ^ (elevado) ; / (divisão, fração) )
carlacristinaf60:
essa é a 6 kk
Perguntas interessantes
Matemática,
7 meses atrás
Química,
7 meses atrás
Português,
7 meses atrás
Matemática,
9 meses atrás
Matemática,
9 meses atrás
Geografia,
1 ano atrás
Química,
1 ano atrás
Saúde,
1 ano atrás